3D-Printed Dual-Mode Invar Channel Filters for Ku-Band Satellite Payloads - Talal Skaik; Emelia Hayward; EL-Moez A. Abd Mohamed; Moataz M. Attallah; Lu Qian; Cesar Miquel Espana; Paul Booth; Yi Wang (IEEE Journal of Microwaves)
This paper presents an end-to-end process of realization of channel filters for output multiplexers (OMUX) in satellite payloads. The filters are designed at 11.609 GHz using dual-mode cylindrical resonators operating at TE113 degenerate modes. Two filters were fabricated from Invar alloy, making use of its low coefficient of thermal expansions (CTE) of 1-2 ppm/K, using powder bed fusion with laser beam (PBF-LB) process. The first filter, as a reference design for comparison purpose, is comprised of four pieces assembled using screws, while the second filter was printed monolithically as one part. The paper presents various design solutions to significantly reducing the filter weight. This includes hollowed flanges and reduced wall thickness, around 0.5 mm, and using waffle structure with reinforcing ribs. The monolithic printed filter offers a weight reduction of 65% compared to the four-piece filter. Post processing techniques including vibratory grinding polishing and silver plating were applied. Both filters were tuned using tuning screws and the measurements are in good agreement with the simulated results. The RF-thermal measurements showed negligible frequency shift confirming the temperature stability for high-power operation in satellite environment.